2020
DOI: 10.1186/s13765-020-00500-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity and abundance of nitrogen cycle-related genes in paddy soil

Abstract: The nitrogen cycle and the associated microbes play an important role in natural ecosystems, including terrestrial habitats; they also have a major effect on climate change. The aim of this study was to explore microbial communities in rice paddy soil by detecting and quantifying some key functional genes involved in the nitrogen cycle using molecular techniques such as conventional polymerase chain reaction (PCR), clone library construction, sequencing, phylogenetic analysis, and real-time PCR. The genes anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The regulation of nitrogen cycling in the contaminated soil is vital to keep the soil microbial communities active and improve their potential to use the contaminant(s) as the sources of energy. Therefore, the status of ammonia oxygenase enzyme (encoded by amoA), nitrogenase enzyme (encoded by nifH, nifD, and nifK), nitrogen oxide reductase (nirK, nirS, and nosZ), and hydrazine synthase (hzsA mediated by annamox) can be the significant indices to determine the soil condition (Rubio and Ludden, 2002;Khanal and Lee, 2020). The present study indicated that nitrogen FIGURE 6 | PCA biplot depicting the taxonomic and functional gene markers of diverse microbial groups and treatments in crude oil fortified sandy loam soil [T1-soil; T2-soil + crude oil (1%); T3-soil + crude oil (1%) + bacterial consortia (Pseudomonas sp.…”
Section: Diversity Of Microbial Groups In the Crude Oil-fortified Sandy Loam Soilmentioning
confidence: 99%
“…The regulation of nitrogen cycling in the contaminated soil is vital to keep the soil microbial communities active and improve their potential to use the contaminant(s) as the sources of energy. Therefore, the status of ammonia oxygenase enzyme (encoded by amoA), nitrogenase enzyme (encoded by nifH, nifD, and nifK), nitrogen oxide reductase (nirK, nirS, and nosZ), and hydrazine synthase (hzsA mediated by annamox) can be the significant indices to determine the soil condition (Rubio and Ludden, 2002;Khanal and Lee, 2020). The present study indicated that nitrogen FIGURE 6 | PCA biplot depicting the taxonomic and functional gene markers of diverse microbial groups and treatments in crude oil fortified sandy loam soil [T1-soil; T2-soil + crude oil (1%); T3-soil + crude oil (1%) + bacterial consortia (Pseudomonas sp.…”
Section: Diversity Of Microbial Groups In the Crude Oil-fortified Sandy Loam Soilmentioning
confidence: 99%
“…The present study identifies a few nitrifying bacteria in EKW using molecular and computational techniques. A similar experiment was conducted by Khanal and Lee (2020), and established that these attempts provide better potential for analysis and assessment of AOB and NOB. In our study, we found nitrifying bacteria in EKW by analysing the phylogenetic relationship of 16S rRNAgene clusters.…”
Section: Resultsmentioning
confidence: 92%
“…amoA is the most relevant gene of AOB, thus they are widely used in community analysis research of water bodies and soil (He et al 2018;Malinowski et al 2020). nxrA gene is present in NOB and codes for the alpha subunit of nitrite oxidoreductase (Rani et al 2016) and helps in the oxidation of nitrite to nitrate (Khanal and Lee 2020). nxrA gene is widely used for the identification of NOB from different environmental samples (Ouyang and Norton 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological nitrogen fixation (BNF) is a key step in the nitrogen cycle as it transforms atmospheric nitrogen into ammonium (Pereira e Silva et al, 2013). The nitrogen cycle and the related microorganisms play crucial roles in the ecosystem, affecting both the agricultural field and climate sectors (Khanal and Lee, 2020). Strain G-1-1-14 T showed a direct association with the nitrogen cycle as it reported the ability to fix atmospheric nitrogen.…”
Section: Genome Analysismentioning
confidence: 99%